Bitcoin Adoption as a Financial Strategy to Maximize Market Capitalization for PT. Digi Nusa Indonesia - Muhammad Reza Priansyah; Raden Aswin Rahadi (Badan Penerbit STIEPARI Press, 2025)
PT. Digi Nusa Indonesia, a pseudonym for a State-Owned Enterprise in Indonesia, faces challenges in increasing its market capitalization beyond IDR Rp250 trillion due to macroeconomic challenges like a strong US dollar and high interest rates. With mostly foreign investors, it faces currency risks and relies on conventional hedging instruments, highlighting the need for innovative strategies. Bitcoin adoption offers a promising alternative, as shown by companies like Strategy and Metaplanet that used it to protect against inflation and currency risk, boosting market capitalization. This research analyzes Bitcoin's potential for PT. Digi Nusa Indonesia, regulatory challenges, and recommends the Hybrid Approach combining Lump Sum and Dollar-Cost Averaging, identified via FAHP-TOPSIS analysis. Regulatory reviews cover OJK POJK No. 27/2024 and Ministry of Finance No. 68/PMK.03/2022. The study presents a practical, compliant framework for integrating Bitcoin into corporate strategy, offering a model for firms aiming to enhance valuation and navigate complex regulations through innovative digital asset use.